PENGHINDARAN PAJAK PERUSAHAAN MULTINASIONAL: PENGARUH INTENSITAS MODAL, KAPITALISASI TIPIS, DAN HARGA TRANSFER DENGAN MODERASI NEGARA SURGA PAJAK: PENGHINDARAN PAJAK OF MULTINATIONAL COMPANIES: THE EFFECT OF CAPITAL INTENSITY, THIN CAPITALIZATION, AND HARGA TRANSFER WITH THE MODERATING ROLE OF TAX HAVENS - Gusharita, Ulpa; Ratnawati, Vince; Zarefar, Arumega (Universitas Riau, 2025)
The purpose of this study is to analyze the effect of capital intensity, thin capitalization, and harga transfer on penghindaran pajak, and to examine the role of tax havens country in strengthening the effect of capital intensity, thin capitalization, and harga transfer on penghindaran pajak. Method is the sufficient information This research approach consists of quantitative and qualitative approaches. The data analysis technique used in this research is multiple linear regression. The sampling technique used was purposive sampling with a sample size of 105 companies, namely multinational companies listed on the IDX in 2016-2022 and selected based on predetermined criteria. Based on the analysis and findings in this study are Capital intensity, thin capitalization, Harga transfer, has an effect on penghindaran pajak and Tax havens country moderates the effect of Capital Intensity, thin capitalization and harga transfer on Penghindaran pajak.